Integrated Device for Cancer Nucleic Acid Biomarker Detection at Body Temperature - Chang Chen; Bin Wu; Xuesong Li; Yuhang Jin; Hangyu Zhang; Bo Liu; Zhengyao Zhang; Na Li (Micromachines)
The quantitative analysis of nucleic acid markers is extensively utilized in cancer detection. However, it faces significant challenges, such as the need for specialized detection devices and the inherent complexity of testing procedures. To address these issues, this study proposes a simplified, rapid, and user-friendly platform for cancer nucleic acid marker detection. We firstly designed a polydimethylsiloxane (PDMS) device for the isothermal amplification reaction of nucleic acid biomarkers based on reverse-transcription recombinase-aided amplification (RT-RAA) technology. Specifically, three potential cancer nucleic acid biomarkers, carcinoembryonic antigen (CEA), prostate-specific antigen (PSA), and prostate cancer antigen 3 (PCA3) were amplified from human serum or urine samples in the PDMS device at body temperature. The reaction chamber was directly integrated with nucleic acid test strips labeled with colloidal gold nanoparticles, allowing for the visual observation of the detection results for the amplification products. The optimal reaction conditions, such as pH, reaction time, antibody, and streptavidin concentration, were defined after a series of optimization studies. The findings demonstrated that the optimal RT-RAA reaction time was 20 min, the primary antibodies were labeled with colloidal gold to the greatest extent at pH 8.5, and the optimal concentrations of secondary antibody and streptavidin were 1.0 mg/mL and 0.5 mg/mL, respectively. Furthermore, this novel detection approach could not only exhibit excellent sensitivity and specificity but also show high accuracy for the analysis of nucleic acid biomarkers in both clinical serum and urine samples. Therefore, the simplified and more convenient operation platform provides a new insight for the semi-quantitative analysis of cancer nucleic acid biomarkers and the rapid screening of early cancer, thereby offering a promising alternative to oncological point-of-care testing (POCT) diagnostics.